The Effect of Annealing Temperature on Spin-Coated Zn-doped NiO film for humidity sensing applications / N.F.Q. Fahmi … [et al.] - Mamat, Mohamad Hafiz; Parimon, Norfarariyanti; Zoolfakar, Ahmad Sabirin; Abdul Razak, Abdul Hadi; Banu, I.B. Shameem; Rusop, Mohamad (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Zinc (Zn)-doped nickel oxide (NiO) thin films were fabricated using spin coating technique for humidity sensing applications. Nickel acetate tetrahydrate was used as a precursor material and zinc acetate was used as the dopant source. The films were annealed at various annealing temperatures of 400 ºC, 500 ºC and 550 ºC in ambient. X-ray diffraction (XRD) was used to investigate the structural properties of the samples, while ultraviolet-visible spectroscopy (UV-Vis) was used to characterize the optical properties of the samples. The thickness of the samples was measured using a surface profiler which the thickness are 178.8 nm, 148.0 nm, and 116.9 nm for samples annealed at 400 ºC, 500 ºC and 550 º, respectively. The humidity sensing properties for each sample were characterized using humidity chamber equipped with humidity sensing measurement system which the relative humidity (RH) value was set between 40% RH and 90% RH. The XRD results showed that all samples were in the amorphous state. The average transmittance in the visible region obtained from the UV-vis spectra exceeded 90% transmission for all samples. The highest bandgap obtained is 3.6 eV for Zn-doped NiO annealed at 500 ºC. The humidity sensing results show that a high sensitivity sensor could be produced using sample annealed at 550 ºC.